Short-range graphite and closed pore synergistic hard carbon negative electrode material and preparation method thereof
By using biomass soybean residue to prepare hard carbon negative electrode materials, temperature regulation and high-temperature treatment of argon and hydrogen conditions are adopted, the problem of insufficient sodium storage performance of existing hard carbon negative electrode materials is solved, and efficient sodium ion battery performance is achieved.
Patent Information
- Application Number
- CN202411771240.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The existing hard carbon anode materials have insufficient sodium storage performance in sodium ion batteries and are unevenly distributed in closed pores, which affects their rate performance and kinetics.
Biomass bean dregs are used as raw materials, and pre-carbonization is performed through temperature regulation under argon conditions, and then treated at high temperature under a reduction atmosphere containing hydrogen to prepare a hard carbon negative electrode material with a short-range graphite structure and closed pores.
It has achieved excellent sodium storage performance of hard carbon negative electrode materials, with the first Coulomb efficiency as high as 88.1%, the first charging specific capacity is 335.2 mAh/g, and the process is simple and suitable for large-scale industrial manufacturing.
Smart Images

Figure CN119528115A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy materials, and in particular to a short-range graphite-like and closed-pore synergistic hard carbon negative electrode material and a preparation method thereof. Background Art
[0002] Sodium is the seventh most abundant element on Earth and is widely found in seawater and terrestrial minerals. Compared with lithium resources, sodium resources are more abundant and less expensive, which makes sodium-ion batteries have potential advantages in large-scale energy storage applications. In the research of sodium-ion batteries, the selection of negative electrode materials is crucial because it directly affects the energy density, cycle stability and safety of the battery. Among the many candidate materials, hard carbon materials have attracted widespread attention due to their excellent performance.
[0003] Among the many raw materials for the preparation of hard carbon materials, biomass raw materials stand out for their abundant sources, sustainability, environmental friendliness and cost-effectiveness. The use of biomass raw materials can not only reduce production costs, but also reduce environmental pollution caused by the large-scale incineration of waste. Furthermore, biomass forms defects and pores during its natural growth process, and can still retain its microscopic morphology after carbonization. In the subsequent heat treatment stage, these structures can be transformed into closed-pore structures, thereby significantly improving their sodium storage performance and showing excellent sodium storage capacity, which indicates its great potential to become a new generation of low-cost, high-performance sodium-ion battery negative electrode materials.
[0004] Due to the above characteristics, the graphite domains (carbon layers) formed after carbonization of biomass raw materials and the closed pores composed of them have become the research objects. The closed pore structure is crucial in the design of hard carbon negative electrode materials for sodium ion batteries, which helps to improve the sodium storage performance of the battery in the low voltage platform area, thereby promoting its potential in commercial applications. However, its formation mechanism is still controversial. Studies have shown that the formation of closed pores in hard carbon may be related to the decomposition, composition and curling of the precursor. In the literature "Understanding theSodium Storage Behavior of Closed Pores / Carbonyl Groups in Hard Carbon. ACS No2024, 18(32), 21491-21503.", the authors treated the precursor with sulfuric acid to increase the carbonyl content of the precursor, thereby affecting the graphite domains formed after carbonization and producing abundant closed pores. However, this treatment method often makes the closed pore wall thicker and increases the long-range ordered graphite-like structure, which in turn affects its rate performance and faster kinetics. Patents (CN109921020A, CN113666356A) mention mixing a carbon source precursor with chemical reagents (such as hydrogen peroxide, nitric acid, and sulfuric acid) for treatment to increase the closed-pore content, but this often changes other properties of the material, resulting in a long-range ordered graphite structure or uneven closed-pore distribution and thicker pore walls.
[0005] Therefore, there is an urgent need to develop a suitable new method to prepare hard carbon negative electrode materials that simultaneously meet the requirements of high closed-pore content and short-range graphite-like structure. Summary of the invention
[0006] The purpose of the present invention is to provide a hard carbon negative electrode material with short-range graphite-like structure and closed pores and a preparation method thereof. The present invention uses biomass bean dregs as raw materials, and obtains a pre-carbonized material by temperature control under argon conditions without adding any chemical reagents. Then, the pre-carbonized material is treated at high temperature under a reducing atmosphere containing hydrogen to prepare a hard carbon negative electrode material with short-range graphite-like structure and closed pores.
[0007] The short-range graphite-like microcrystalline structure of the hard carbon negative electrode material prepared by the present invention enables it to have more sodium embedding sites, and the abundant closed pores provide a good platform capacity, thereby achieving excellent sodium storage performance.
[0008] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows: A method for preparing a short-range graphite-like and closed-pore hard carbon negative electrode material comprises the following steps: (1) Wash the dregs with distilled water and dry them in a forced air drying oven; (2) placing the dried bean dregs in a tube furnace and pre-carbonizing them in an argon or nitrogen atmosphere to obtain a pre-carbonized material 1; (3) washing the pre-carbonized material 1 obtained in step (2) with dilute hydrochloric acid and deionized water until the washing liquid is neutral to obtain pre-carbonized material 2; (4) The pre-carbonized material 2 obtained in step (3) is placed in a high-temperature furnace and subjected to high-temperature carbonization in an atmosphere containing hydrogen reduction, wherein the short-range graphite domain crystallites of the pre-carbonized material 2 continue to grow and bend to form closed pores, and at the same time, some short-range graphite domain crystallites stop growing, thereby obtaining a hard carbon negative electrode material rich in short-range graphite and closed pores.
[0009] Preferably, in step (1), the drying temperature of the okara is 80° C. and the drying time is 12 h.
[0010] It should be noted that the pre-carbonization temperature will affect the development of the carbon layer and the formation of closed pores, which will ultimately affect the performance of the material; and the pre-carbonization treatment time should not be too long. If the treatment time is too long, the carbon layer will be too thick, which will affect the specific capacity or first coulombic efficiency of the hard carbon material.
[0011] Preferably, the pre-carbonization temperature in step (2) is between 450-850 °C and the pre-carbonization time is 2-5 h to ensure that the okara components are fully carbonized and decomposed. Too high a pre-carbonization temperature will result in additional energy consumption and excessive development of the carbon layer, while too low a pre-carbonization temperature may result in incomplete carbonization of the hard carbon material in subsequent high-temperature treatment. This incomplete carbonization may damage the reversible specific capacity of the hard carbon material, thereby affecting the overall electrochemical performance of the material.
[0012] Further preferably, the pre-carbonization temperature in step (2) is 700-750°C and the pre-carbonization time is 2 h.
[0013] Preferably, the pre-carbonization heating rate in step (2) is 2-10 °C / min.
[0014] Preferably, the concentration of the dilute hydrochloric acid in step (3) is 1-2 mol / L, and the pickling time is 6 h, to ensure that impurities in the pre-carbonized material are fully removed.
[0015] The deionized water washing process in step (3) is to use deionized water for repeated filtration and washing, and the number of washing times is preferably 3 to 10 times to ensure the removal of hydrochloric acid.
[0016] Preferably, in step (4), the high temperature carbonization temperature is 1000-1600°C, the heating rate is 2-10°C / min, and the holding time is 2-5 hours. The growth of the graphite-like structure is regulated according to the high temperature carbonization temperature range to ensure that the length of the graphite-like structure is appropriate.
[0017] Further preferably, the high temperature carbonization temperature in step (4) is 1350-1400°C and the time is 2 h.
[0018] Preferably, the high-temperature carbonization protection gas in step (4) is any one of hydrogen, hydrogen-argon, and hydrogen-nitrogen.
[0019] The present invention also provides a hard carbon negative electrode material with short-range graphite-like and closed-pore synergy, and the hard carbon negative electrode material with short-range graphite-like and closed-pore synergy is prepared by the above-mentioned preparation method.
[0020] The present invention also provides a hard carbon negative electrode material with short-range graphite-like and closed-pore synergy as a negative electrode material for sodium ion batteries.
[0021] Beneficial effects: (1) The hard carbon negative electrode material provided by the present invention has a better sodium storage capacity than traditional hard carbon negative electrode materials because of its developed closed-pore structure and short-range graphite-like structure. In addition, the number of open pores in the material is reduced, which helps to improve its first coulombic efficiency. Its first coulombic efficiency is as high as 88.1%, and the first charge specific capacity is 335.2 mAh / g.
[0022] (2) The preparation method of the hard carbon negative electrode material provided by the present invention uses biomass bean dregs as raw material, and through pre-carbonization temperature treatment, the material triggers the curling of the carbon layer during the carbonization process, thereby promoting the formation of more thin-walled closed-pore structures.
[0023] (3) The preparation method of the hard carbon negative electrode material provided by the present invention has the advantages of a wide range of raw material sources and a simple process, which makes it very suitable for large-scale industrial manufacturing environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the HRTEM image of Example 1 of the present invention.
[0025] Figure 2 The first charge and discharge curve of the hard carbon negative electrode material prepared in Example 1 of the present invention for a sodium ion battery at a current density of 20 mA / g.
[0026] Figure 3 The hard carbon negative electrode material prepared in Example 1 of the present invention is used for the rate performance of sodium ion batteries.
[0027] Figure 4 2 are XRD diagrams of Example 1 of the present invention and Comparative Example 1.
[0028] Figure 5 2 are Raman graphs of Example 1 of the present invention and Comparative Example 1.
[0029] Figure 6This is the HRTEM image of Example 3 of the present invention.
[0030] Figure 7 This is the HRTEM image of Example 6 of the present invention. DETAILED DESCRIPTION
[0031] The purpose of the present invention is to provide a hard carbon negative electrode material with short-range graphite-like structure and closed pores and a preparation method thereof. The present invention uses biomass bean dregs as raw materials, and obtains a pre-carbonized material by temperature control under argon conditions without adding any chemical reagents. Then, a high-temperature treatment is performed under hydrogen, hydrogen-argon or hydrogen-nitrogen mixed gas conditions to prepare a hard carbon negative electrode material with short-range graphite-like structure and closed pores.
[0032] The short-range graphite-like microcrystalline structure of the hard carbon negative electrode material prepared by the present invention enables it to have more sodium embedding sites, and the abundant closed pores provide a good platform capacity, thereby achieving excellent sodium storage performance.
[0033] The present invention provides a short-range graphite-like and closed-pore synergistic hard carbon negative electrode material and a preparation method thereof, comprising the following steps: (1) Weigh a certain amount of bean dregs, wash them with distilled water, and then dry them in a forced air drying oven; (2) placing the dried bean dregs in a tube furnace and pre-carbonizing them in an argon or nitrogen atmosphere to obtain a pre-carbonized material 1; (3) washing the pre-carbonized material 1 obtained in step (2) with a dilute hydrochloric acid solution and deionized water until the solution becomes neutral, thereby obtaining a pre-carbonized material 2; (4) The pre-carbonized material obtained in step (3) is placed in a high-temperature furnace and subjected to high-temperature carbonization in a hydrogen, hydrogen-argon or hydrogen-nitrogen atmosphere, wherein the short-range graphite domain crystallites of the pre-treated material continue to grow and bend to form closed pores, while some short-range graphite domain crystallites stop growing, thereby obtaining a hard carbon negative electrode material rich in short-range graphite and closed pores.
[0034] Example 1 A short-range graphite-like and closed-pore synergistic hard carbon negative electrode material and a preparation method thereof, the preparation method comprising the following steps: Step 1, weighing 500 g of bean dregs, washing them with an appropriate amount of distilled water, and placing them in a forced air drying oven at a drying temperature of 80° C. for 12 h to remove impurities and moisture; Step 2, take 10 g of the dried bean dregs and place them in a tubular furnace, heat them to 750 °C at a heating rate of 5 °C / min under an argon or nitrogen atmosphere, keep them warm for 2 h, cool them to room temperature and take them out to obtain pre-carbonized material 1 for washing; carbonization at 750 °C for 2 h is mainly to ensure sufficient pyrolysis of cellulose.
[0035] Step 3, the pre-carbonized material 1 obtained in step 2 is placed in a 1 mol / L hydrochloric acid solution for washing until the washing liquid is neutral, the washing time is 6 hours, and then washed with deionized water until the washing liquid is neutral; and then placed in a blast drying oven at 60° C. for 12 hours to obtain a relatively pure pre-carbonized material 2; Step 4, placing the pure pre-carbonized material obtained in step 3 in a high-temperature tubular furnace, first heating it to 900 ° C at a heating rate of 5 ° C / min in a hydrogen reducing atmosphere, and then heating it to 1400 ° C at a heating rate of 2 ° C / min, keeping it warm for 2 hours, cooling it to room temperature and taking it out to obtain a hard carbon material with short-range graphite and closed pores. Experimental verification shows that keeping at 1400 ° C for 2 hours is the optimal condition for regulating the short-range graphite structure. Too long time or too high temperature will lead to excessive development of graphite domains, and too short time or too low temperature will lead to insufficient development of graphite domains.
[0036] The short-range graphite-like and closed-pore synergistic hard carbon material prepared above is used as the active material of the battery negative electrode material for the preparation of sodium ion batteries.
[0037] According to the mass ratio of 80%: 10%: 10%, 80 mg of hard carbon material, 10 mg of acetylene black and 10 mg of sodium alginate SA were weighed, and an appropriate amount of deionized water was added dropwise. The mixture was stirred for 20 min until a uniform slurry was formed. The slurry was evenly coated on a copper (Cu) foil using a 100 μm scraper and dried in a forced air drying oven for 12 h. The Cu foil with active material was cut into disc-shaped electrode sheets for later use.
[0038] The button cell was assembled in a glove box filled with Ar atmosphere, using the prepared electrode sheet as the negative electrode, commercial electrolyte 1.0 M NaPF6in DME=100 Vol% as the electrolyte, and Na metal sheet as the counter electrode to assemble into a 2032 button cell.
[0039] Figure 1 This is the HRTEM image of the short-range graphite-like and closed-pore synergistic hard carbon negative electrode material prepared in Example 1 of the present invention; as can be seen from the figure, it can be clearly seen that there is a short-range graphite-like microcrystalline structure with high conductivity; at the same time, the short-range graphite-like domains are cross-linked with each other to construct a rich closed-pore structure, which is beneficial to sodium storage in the platform area.
[0040] Figure 2 This is the first cycle charge and discharge curve of Example 1 of the present invention; as shown in the figure, at a current density of 20 mA / g, the first coulombic efficiency is 88.1%, and the first cycle charge capacity is 335.2 mAh / g. The platform capacity contributes 230.9 mAh g -1 , accounting for 68.9%. The high platform capacity share is attributed to the synergistic effect of short-range graphite-like microstructure and closed pores.
[0041] Figure 3 This is the rate performance of Example 1 of the present invention; as can be seen from the figure, at 1 A g -1 The reversible specific capacity is 222.8 mAh g -1 The excellent rate capability can be attributed to the small interlayer spacing and short-range graphite-like microstructure, which give it high electrical conductivity.
[0042] Comparative Example 1 Step 1, weighing 500 g of bean dregs, washing them with an appropriate amount of distilled water, and placing them in a forced air drying oven at a drying temperature of 80° C. for 12 h to remove impurities and moisture; Step 2, take 10 g of the dried bean dregs and place them in a tubular furnace, heat them to 750 °C at a heating rate of 5 °C / min under an argon or nitrogen atmosphere, keep them warm for 2 h, cool them to room temperature and take them out to obtain pre-carbonized material 1 for washing; carbonization at 750 °C for 2 h is mainly to ensure sufficient pyrolysis of cellulose.
[0043] Step 3, the pre-carbonized material 1 obtained in step 2 is placed in a 1 mol / L hydrochloric acid solution for washing for 6 hours, and then washed with deionized water until the washing liquid is neutral; and then placed in a blast drying oven at 60°C for 12 hours to obtain a relatively pure pre-carbonized material 2; Step 4, placing the pure pre-carbonized material obtained in step 3 in a high-temperature tubular furnace, first heating it to 900 °C at a heating rate of 5 °C / min under an argon or nitrogen atmosphere, and then heating it to 1400 °C at a heating rate of 2 °C / min, keeping it at a temperature for 2 h, cooling it to room temperature and taking it out to obtain a hard carbon material.
[0044] Step 5, using the hard carbon material prepared above as the active material of the negative electrode material for the preparation of a sodium ion battery, the specific method is the same as that of Example 1. The assembled half-cell has a first coulombic efficiency of 76.5% and a first cycle charge capacity of 290.4 mAh / g at a current density of 20 mA / g.
[0045] Figure 4 2 are XRD diagrams of Example 1 of the present invention and Comparative Example 1; it can be seen from the figure that the (002) peak of Example 1 moves to a high angle and the material layer spacing decreases, which confirms the short-range graphite-like structure observed in the TEM image.
[0046] Figure 5 3 and 4 are Raman graphs of Example 1 of the present invention and Comparative Example 1. It can be seen from the graph that the disorder degree of Example 1 is obviously lower than that of Comparative Example 1, which can be attributed to the short-range graphite-like structure in Example 1.
[0047] Comparative Example 2 The comparative example of the present invention provides a method for preparing a biomass-based hard carbon negative electrode material for a sodium ion battery, the steps of which include: Step 1, weighing 500 g of bean dregs, washing them with an appropriate amount of distilled water, and placing them in a forced air drying oven at a drying temperature of 80° C. for 12 h to remove impurities and moisture; Step 2, washing the dregs treated in step 1 in a 1 mol / L hydrochloric acid solution for 6 h, and then washing with deionized water until the washing solution is neutral; and then drying in a forced air drying oven at 60° C. for 12 h to obtain a relatively pure dregs raw material; Step 3, taking 10 g of the dried bean dregs and placing them in a high-temperature tube furnace, heating them to 900 °C at a heating rate of 5 °C / min in a hydrogen reducing atmosphere, and then heating them to 1400 °C at a heating rate of 2 °C / min, keeping the temperature for 2 h, cooling them to room temperature and taking them out to obtain a hard carbon material; Step 4, using the hard carbon material prepared above as the active material of the negative electrode material for the preparation of a sodium ion battery, the specific method is the same as that of Example 1. The assembled half-cell has a first coulombic efficiency of 82.2% and a first cycle charge capacity of 281.6 mAh / g at a current density of 20 mA / g.
[0048] Example 2 A short-range graphite-like and closed-pore synergistic hard carbon negative electrode material and a preparation method thereof, the preparation method comprising the following steps: Step 1, weighing 500 g of bean dregs, washing them with an appropriate amount of distilled water, and placing them in a forced air drying oven at a drying temperature of 80° C. for 12 h to remove impurities and moisture; Step 2, taking 10 g of dried bean dregs and placing them in a tube furnace, heating them to 750 °C at a heating rate of 5 °C / min in an argon or nitrogen atmosphere, keeping them at this temperature for 2 h, cooling them to room temperature and taking them out to obtain a pre-carbonized material 1, which is to be washed; Step 3, the pre-carbonized material 1 obtained in step 2 is placed in a 1 mol / L hydrochloric acid solution and deionized water for washing for 6 hours, and then washed with deionized water until the washing liquid is neutral; and then placed in a blast drying oven at 60°C for 12 hours to obtain a relatively pure pre-carbonized material 2; Step 4, placing the pure pre-carbonized material 2 obtained in step 3 in a high-temperature tube furnace, heating it to 900 ° C at a heating rate of 5 ° C / min in a hydrogen atmosphere, and then heating it to 1400 ° C at a heating rate of 2 ° C / min, and keeping it for 2 h. After cooling to room temperature, take it out to obtain a short-range graphite-like and closed-pore synergistic hard carbon negative electrode material; The short-range graphite-like and closed-pore synergistic hard carbon material prepared above is used as the active material of the battery negative electrode material for the preparation of sodium ion batteries.
[0049] According to the mass ratio of 80%: 10%: 10%, 80 mg of hard carbon material, 10 mg of acetylene black, and 10 mg of PVDF were weighed, and an appropriate amount of deionized water was added. The mixture was stirred for 20 min until it became a uniform slurry. The slurry was evenly coated on a copper (Cu) foil using a 100 μm scraper and dried in a forced air drying oven for 12 h. The Cu foil with active material was cut into disc-shaped electrode sheets for later use.
[0050] The button cell was assembled in a glove box filled with Ar atmosphere, using the prepared electrode sheet as the negative electrode, commercial electrolyte 1.0 M NaPF6in DME=100 Vol% as the electrolyte, and Na metal sheet as the counter electrode to assemble into a 2032 button cell.
[0051] The assembled button cell has a first coulombic efficiency of 76.0% and a first cycle charge capacity of 330.1 mAh / g at a current density of 20 mA / g.
[0052] Example 3 A short-range graphite-like and closed-pore synergistic hard carbon negative electrode material and a preparation method thereof, the preparation method comprising the following steps: Step 1, weighing 500 g of bean dregs, washing them with an appropriate amount of distilled water, and placing them in a forced air drying oven at a drying temperature of 80° C. for 12 h to remove impurities and moisture; Step 2, taking 10 g of dried bean dregs and placing them in a tube furnace, heating them to 450 °C at a heating rate of 5 °C / min in an argon or nitrogen atmosphere, keeping them at this temperature for 2 h, cooling them to room temperature and taking them out to obtain a pre-carbonized material 1, to be washed; Step 3, the pre-carbonized material 1 obtained in step 2 is placed in a 1 mol / L hydrochloric acid solution for washing for 6 hours, and then washed with deionized water until the washing liquid is neutral; and then placed in a blast drying oven at 60°C for 12 hours to obtain a relatively pure pre-carbonized material 2; Step 4, placing the pure pre-carbonized material 2 obtained in step 3 in a high-temperature tube furnace, heating it to 900 ° C at a heating rate of 5 ° C / min in a hydrogen atmosphere, and then heating it to 1600 ° C at a heating rate of 2 ° C / min, and keeping it for 2 h. After cooling to room temperature, take it out to obtain a short-range graphite-like and closed-pore synergistic hard carbon negative electrode material; The short-range graphite-like and closed-pore synergistic hard carbon material prepared above is used as the active material of the battery negative electrode material for the preparation of a sodium ion battery, and the specific method is the same as Example 2.
[0053] Figure 6 This is the HRTEM image of the hard carbon negative electrode material prepared in embodiment 3 of the present invention; as can be seen from the figure, it can be clearly seen that the length of the graphite-like microcrystalline structure is significantly increased, and the degree of graphitization is increased; at the same time, the closed-pore structure is significantly reduced, which is not conducive to sodium storage.
[0054] Example 4 A short-range graphite-like and closed-pore synergistic hard carbon negative electrode material and a preparation method thereof, the preparation method comprising the following steps: Step 1, weighing 500 g of bean dregs, washing them with an appropriate amount of distilled water, and placing them in a forced air drying oven at a drying temperature of 80° C. for 12 h to remove impurities and moisture; Step 2, taking 10 g of dried bean dregs and placing them in a tube furnace, heating them to 650 °C at a heating rate of 5 °C / min in an argon or nitrogen atmosphere, keeping them at this temperature for 2 h, cooling them to room temperature and taking them out to obtain a pre-carbonized material 1, which is to be washed; Step 3, the pre-carbonized material 1 obtained in step 2 is placed in a 1 mol / L hydrochloric acid solution for washing for 6 hours, and then washed with deionized water until the washing liquid is neutral; and then placed in a blast drying oven at 60°C for 12 hours to obtain a relatively pure pre-carbonized material 2; Step 4, the pure pre-carbonized material obtained in step 3 is placed in a high-temperature tube furnace, and the temperature is first increased to 900 ° C at a heating rate of 5 ° C / min in a hydrogen atmosphere, and then increased to 1400 ° C at a heating rate of 2 ° C / min, and the heat preservation time is 2 h. After cooling to room temperature, the short-range graphite-like and closed-pore synergistic hard carbon negative electrode material is obtained. Step 5, using the short-range graphite-like and closed-pore synergistic hard carbon material prepared above as the active material of the battery negative electrode material for the preparation of a sodium ion battery, the specific method is the same as Example 2.
[0055] Example 5 A short-range graphite-like and closed-pore synergistic hard carbon negative electrode material and a preparation method thereof, the preparation method comprising the following steps: Step 1, weighing 500 g of bean dregs, washing them with an appropriate amount of distilled water, and placing them in a forced air drying oven at a drying temperature of 80° C. for 12 h to remove impurities and moisture; Step 2, taking 10 g of dried bean dregs and placing them in a tube furnace, heating them to 850 °C at a heating rate of 5 °C / min in an argon or nitrogen atmosphere, keeping them at this temperature for 2 h, cooling them to room temperature and taking them out to obtain a pre-carbonized material 1, which is to be washed; Step 3, the pre-carbonized material 1 obtained in step 2 is placed in a 1 mol / L hydrochloric acid solution for washing for 6 hours, and then washed with deionized water until the washing liquid is neutral; and then placed in a blast drying oven at 60°C for 12 hours to obtain a relatively pure pre-carbonized material 2; Step 4, placing the pure pre-carbonized material 2 obtained in step 3 in a high-temperature tube furnace, heating it to 900 ° C at a heating rate of 5 ° C / min in a hydrogen atmosphere, and then heating it to 1400 ° C at a heating rate of 2 ° C / min, and keeping it for 2 h. After cooling to room temperature, take it out to obtain a short-range graphite-like and closed-pore synergistic hard carbon negative electrode material; The short-range graphite-like and closed-pore synergistic hard carbon material prepared above is used as the active material of the battery negative electrode material for the preparation of a sodium ion battery, and the specific method is the same as Example 2.
[0056] Example 6 A short-range graphite-like and closed-pore synergistic hard carbon negative electrode material and a preparation method thereof, the preparation method comprising the following steps: Step 1, weighing 500 g of bean dregs, washing them with an appropriate amount of distilled water, and placing them in a forced air drying oven at a drying temperature of 80° C. for 12 h to remove impurities and moisture; Step 2, taking 10 g of dried bean dregs and placing them in a tube furnace, heating them to 900 °C at a heating rate of 5 °C / min in an argon or nitrogen atmosphere, keeping them at this temperature for 2 h, cooling them to room temperature and taking them out to obtain a pre-carbonized material 1, which is to be washed; Step 3, the pre-carbonized material 1 obtained in step 2 is placed in a 1 mol / L hydrochloric acid solution for washing for 6 hours, and then washed with deionized water until the washing liquid is neutral; and then placed in a blast drying oven at 60°C for 12 hours to obtain a relatively pure pre-carbonized material 2; Step 4, placing the pure pre-carbonized material 2 obtained in step 3 in a high-temperature tube furnace, heating it to 900 ° C at a heating rate of 5 ° C / min in a hydrogen atmosphere, and then heating it to 1000 ° C at a heating rate of 2 ° C / min, and keeping it for 2 h. After cooling to room temperature, take it out to obtain a short-range graphite-like and closed-pore synergistic hard carbon negative electrode material; The short-range graphite-like and closed-pore synergistic hard carbon material prepared above is used as the active material of the battery negative electrode material for the preparation of a sodium ion battery, and the specific method is the same as Example 2.
[0057] Figure 7 This is the HRTEM image of the hard carbon negative electrode material prepared in Example 6 of the present invention. As can be seen from the figure, it can be clearly seen that the graphite-like microcrystalline structure is significantly reduced, and the degree of graphitization is reduced, resulting in lower conductivity; at the same time, the open pores cannot be closed to form a closed-pore structure, thereby resulting in a decrease in sodium storage capacity.
[0058] The performance of the battery assembled with the materials obtained in the above examples and comparative examples was tested, and the results are shown in Table 1.
[0059] Table 1 Performance parameters of assembled half-cells
[0060] It can be seen from the above embodiments and comparative examples that after the bean dregs in Example 1 are carbonized at high temperature, the reversible specific capacity of the material can reach 335.2 mAh / g and the first coulombic efficiency can reach 88.1%. Since the bean dregs in Comparative Example 2 have not been pre-carbonized, the surface defect content of the material after high-temperature carbonization is high, and the excessively long graphite layer hinders the formation of closed pores, and fails to form effective closed pores, thereby affecting its first coulombic efficiency and specific capacity. In Example 2, compared with Example 1, only the binder is replaced with PVDF, and the first efficiency of the hard carbon material finally obtained is reduced, and the specific capacity does not change significantly. Further increasing the pre-carbonization treatment temperature, in Example 6 of the present invention, because the pre-carbonization treatment temperature is not controlled in the optimal range, this causes the carbon layer to grow too long, which will hinder the formation of closed pores, and its first coulombic efficiency is about 70%, and the reversible specific capacity is only 251.8 mAh / g.
[0061] In summary, the preparation method proposed in the present invention relies on the coordination of the composition ratios of the components and the process steps. It is this synergistic effect that gives the biomass-based hard carbon material excellent electrochemical properties. If any condition deviates from the range specified in the present invention, it may cause the performance of the hard carbon material to decrease.
[0062] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and the description only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention to be protected. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a hard carbon negative electrode material with short-range graphite and closed pores, characterized in that: The following steps are involved: (1) Wash the dregs with distilled water and dry them in a forced air drying oven; (2) placing the dried bean dregs in a tube furnace and pre-carbonizing them in an argon or nitrogen atmosphere to obtain a pre-carbonized material 1; (3) washing the pre-carbonized material 1 obtained in step (2) with dilute hydrochloric acid and deionized water until the washing liquid is neutral to obtain pre-carbonized material 2; (4) The pre-carbonized material obtained in step (3) is placed in a high-temperature furnace and subjected to high-temperature carbonization in an atmosphere containing hydrogen reduction, thereby obtaining a hard carbon negative electrode material rich in short-range graphite and closed-pore synergy.
2. The method for preparing a hard carbon negative electrode material with short-range graphite and closed pores according to claim 1, characterized in that: In step (1), the drying temperature of the okara is 80°C and the drying time is 12 h.
3. The method for preparing a hard carbon negative electrode material with short-range graphite and closed pores according to claim 1, characterized in that: The pre-carbonization temperature in step (2) is 450-850°C, and the pre-carbonization time is 2-5 h. Preferably, the pre-carbonization temperature in step (2) is 700-750°C, and the pre-carbonization time is 2 h.
4. The method for preparing a hard carbon negative electrode material with short-range graphite-like and closed-pore synergy according to claim 1, characterized in that: The pre-carbonization heating rate in step (2) is 2-10 °C / min.
5. The method for preparing a hard carbon negative electrode material with short-range graphite-like and closed-pore synergy according to claim 1, characterized in that: The concentration of the dilute hydrochloric acid in step (3) is 1-2 mol / L, and the pickling time is 6 h.
6. The method for preparing a hard carbon negative electrode material with short-range graphite and closed pores according to claim 1, characterized in that: The deionized water washing process in step (3) is to use deionized water for repeated filtration and washing, and the number of washing times is 3 to 10 times.
7. The method for preparing a hard carbon negative electrode material with short-range graphite and closed pores according to claim 1, characterized in that: The high-temperature carbonization temperature in step (4) is 1000-1600°C, the heating rate is 2-10°C / min, and the insulation time is 2-5 h; preferably, the high-temperature carbonization temperature in step (4) is 1350-1400°C; the time is 2 h.
8. The method for preparing a hard carbon negative electrode material with short-range graphite and closed pores according to claim 1, characterized in that: The high-temperature carbonization protection gas in step (4) is any one of hydrogen, hydrogen-argon, and hydrogen-nitrogen.
9. A hard carbon negative electrode material with short-range graphite-like and closed-pore synergy, prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the short-range graphite-like and closed-pore synergistic hard carbon negative electrode material as claimed in claim 9 in negative electrode materials for sodium ion batteries.
Citation Information
Patent Citations
Method for preparing high-capacity hard carbon negative electrode material of lithium ion battery
CN109921020A
Hard carbon negative electrode material of sodium-ion battery based on shell biomass and preparation method of hard carbon negative electrode material
CN113666356A
Direction control method of surface oxygen functional groups on coal-based hard carbon for sodium-storing cathodes
CN109796003A
High-energy-density sodium ion battery
CN114373928A
Method for improving electrochemical performance of biomass hard carbon as sodium battery negative electrode
CN115028157A